Computational Science Stack Exchange is a question and answer site for scientists using computers to solve scientific problems. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider $n$ integer-valued and independent random variables $e_1, e_2, \dots, e_n$ with known distribution functions $m_1, m_2, \dots, m_n$. Let's denote with $E^{1..n}$ the random variable given by the sum of $e_1, e_2, \dots e_n$, that is $E^{1..n} = \displaystyle\sum_i{e_i}$. The PDF of $E^{1..n}$, $m^{1..n}$, is given by the convolution of $m_1, m_2, \dots, m_n$.

I would like to calculate $P(E^{1..n} = 1 \,| \,e_1 = 1)$.

My intuition tells that that this is equal to $P(E^{2..n} = 0) P(e_1=1)$ but I just can't figure out the math behind it.

share|improve this question
This would be a better place for your question: – Dr_Sam Feb 26 '13 at 7:24
But the answer is no: $P(E^{1..n} = 1 | e_1 = 1)$ = $P(E^{2..n} + e_1 = 1 | e_1 = 1)$ = $P(E^{2..n} = 0 | e_1 = 1)$ = $P(E^{2..n} = 0)$ because of the independance. – Dr_Sam Feb 26 '13 at 8:06
Yes, you're right, thanks! – user92382 Feb 26 '13 at 9:27
@Dr_Sam: Please post your comment as an answer, so the OP can accept it. – Paul Feb 27 '13 at 0:23
up vote 1 down vote accepted

As said in my comments of the question, a better place for asking this kind of question would be on the math part of stackexchange.

However, we can find

$P(E^{1..n}=1|e_1=1) = P(E^{2..n}+e_1=1|e_1=1) = P(E^{2..n}=0|e_1=1) = P(E^{2..n}=0)$,

the last equality being the result of the independance of the $e_i$.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.